The Wedding of Workfare and Prisonfare Revisited - Wacquant, Loïc (Social justice, 2011)
An interview is presented with sociologist Loïc Wacquant, author of "Punishing the Poor: The Neoliberal Government of Social Insecurity." He discusses his theoretical approach to understanding criminal justice trends, such as the rising incarceration rate, in relation to political-economic changes in the U.S. and Europe. He describes prisons and welfare programs as twin policies for dealing with the segment of the population impoverished by neoliberal economic and political policies.